Submission to Secretariat des Commissions Assemblee Nationale on the Place of Religion in Schools - Quebec Federation of Home and School Associations (QFHSA) (1999)
The Report of the Task Force on the Place of Religion in Schools in Quebec and its recommendations have been studied by the QFHSA's Education Committee and discussed with our members within a very restricted time frame. Although there are sections of the report that produced responses to which a majority of the participants were in agreement, there are also sections that produced far more diverse opinions about the nature of this submission.

Island Schools - Goodwin, Amanda (1997)

Quebec Home & School News - Quebec Federation of Home and School Associations (QFHSA) (1996)

Quebec Home & School News - Quebec Federation of Home and School Associations (QFHSA) (1996)

Quebec Home & School News - Quebec Federation of Home and School Associations (QFHSA) (1996)

Quebec Home & School News - Quebec Federation of Home and School Associations (QFHSA) (1996)

Quebec Home & School News - Quebec Federation of Home and School Associations (QFHSA) (1995)

Quebec Home & School News - Quebec Federation of Home and School Associations (QFHSA) (1995)

Quebec Home & School News - Quebec Federation of Home and School Associations (QFHSA) (1995)

Quebec Home & School News - Quebec Federation of Home and School Associations (QFHSA) (1995)

Quebec Home & School News - Quebec Federation of Home and School Associations (QFHSA) (1994)

Quebec Home & School News - Quebec Federation of Home and School Associations (QFHSA) (1994)

Quebec Home & School News - Quebec Federation of Home and School Associations (QFHSA) (1994)

Quebec Home & School News - Quebec Federation of Home and School Associations (QFHSA) (1994)

Quebec Home & School News - Quebec Federation of Home and School Associations (QFHSA) (1993)

Quebec Home & School News - Quebec Federation of Home and School Associations (QFHSA) (1993)

Quebec Home & School News - Quebec Federation of Home and School Associations (QFHSA) (1993)

Quebec Home & School News - Quebec Federation of Home and School Associations (QFHSA) (1993)

Quebec Home & School News - Quebec Federation of Home and School Associations (QFHSA) (1993)

Quebec Home & School News - Quebec Federation of Home and School Associations (QFHSA) (1992)

Quebec Home & School News - Quebec Federation of Home and School Associations (QFHSA) (1992)

Quebec Home & School News - Quebec Federation of Home and School Associations (QFHSA) (1992)

Quebec Home & School News - Quebec Federation of Home and School Associations (QFHSA) (1992)

Quebec Home & School News - Quebec Federation of Home and School Associations (QFHSA) (1991)

Quebec Home & School News - Quebec Federation of Home and School Associations (QFHSA) (1991)

Quebec Home & School News - Quebec Federation of Home and School Associations (QFHSA) (1991)

Quebec Home & School News - Quebec Federation of Home and School Associations (QFHSA) (1991)

Quebec Home & School News - Quebec Federation of Home and School Associations (QFHSA) (1990)

Quebec Home & School News - Quebec Federation of Home and School Associations (QFHSA) (1990)

Quebec Home & School News - Quebec Federation of Home and School Associations (QFHSA) (1990)